1994
DOI: 10.1029/94gl00420
|View full text |Cite
|
Sign up to set email alerts
|

Subdaily Earth rotation during the Epoch ‘92 campaign

Abstract: Global Positioning System (GPS) data were used to estimate Earth rotation variations over an 11‐day period during the Epoch ‘92 campaign in the summer of 1992. Earth orientation was measured simultaneously by several very long baseline interferometry (VLBI) networks. GPS and VLBI estimates of UT1 with 3‐hour time resolution were then compared and analyzed. The high frequency behavior of both data sets is similar, although drifts between the two series of ∼0.1 ms over 2‐5 days are evident. The geodetic results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The variations in Earth rotation seen at high frequencies (periods of 1 day and shorter) are mainly the result of changes in the ocean heights and currents due to the tidal potential generated by the Sun and Moon. Apart from these tidal effects of the oceans some atmospheric excitation of PM and UT1 is to be expected at diurnal and semidiurnal frequencies [Freedman et al, 1994; Herring and Dong, So far, papers discussing subdaily Earth rotation parameters derived from GPS data were concentrating on results stemming from intensive campaigns of 1 or 2 weeks (e.g., from GIG'91 [Lichten et al, 1992], Epoch'92 [Freedman et al, 1994], CONT'94 [Weber, 1996], or from other short time intervals [Grejner-Brzezinska and Goad, 1996]). These investigations showed that the high-frequency variations of Earth rotation due to the ocean tides may be measured by GPS.…”
Section: Introductionmentioning
confidence: 99%
“…The variations in Earth rotation seen at high frequencies (periods of 1 day and shorter) are mainly the result of changes in the ocean heights and currents due to the tidal potential generated by the Sun and Moon. Apart from these tidal effects of the oceans some atmospheric excitation of PM and UT1 is to be expected at diurnal and semidiurnal frequencies [Freedman et al, 1994; Herring and Dong, So far, papers discussing subdaily Earth rotation parameters derived from GPS data were concentrating on results stemming from intensive campaigns of 1 or 2 weeks (e.g., from GIG'91 [Lichten et al, 1992], Epoch'92 [Freedman et al, 1994], CONT'94 [Weber, 1996], or from other short time intervals [Grejner-Brzezinska and Goad, 1996]). These investigations showed that the high-frequency variations of Earth rotation due to the ocean tides may be measured by GPS.…”
Section: Introductionmentioning
confidence: 99%
“…With the planned 512 Mb/s recording and a network with wider geographical coverage, the sub-daily precision is expected to be better than earlier CONT campaigns, thus clarifying even more the deviations from the existing ocean tide model and allowing further testing of other theoretical models [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 97%
“…Since the 1980s, a Kalman filter, the Kalman Earth Orientation Filter (KEOF), has been used at the Jet Propulsion Laboratory (JPL) to combine and predict EOPs in support of interplanetary spacecraft tracking and navigation (Freedman et al, 1994a;Gross et al, 1998). A Kalman filter has many properties that make it an attractive method of combining Earth orientation series.…”
Section: Intertechnique Combinationsmentioning
confidence: 99%